(untitled) (Vietnam Journal of Community Medicine, 2024)
Research objective: Determine the antibacterial activity of the whole extract of the plant collected in Nghe An Research method: Using the ultrasonic extraction with two solvents, ethanol and methanol, to obtain a highly concentrated extract and test the antibacterial activity on some common bacterial strains. Results: It was noted that the total extract with solvents ethanol 700 and methanol 800 were effective against S.aureus and K.pneumoniae, but had no effect on other bacteria (E.coli, P. aeruginosa, H .influenzae…). The diameter of the sterile zone of the ethanol 700 and methanol 800 extracts on S. aureus was 10.3 ± 0.95mm and 9.98 ± 0.89 mm (10.3 ± 0.95mm), respectively, larger than that on the K.pneumoniae strain. with values of 8.72 ± 0.87mm, 7.56 ± 0.81mm respectively. Conclusion: Achyranthes aspera L. collected in Nghe An and extracted by ultrasonic extraction method with ethanol and methanol solvents, give the extract an antibacterial effect on two strains of S.aureus and K.pneumonia. It can be a source of natural antibiotics for more research.